Modeling and Prediction of Conducted Interference ofElectric Vehicle Motor Drive System - LIU Songlin; YANG Tianfan; ZHI Yongjian; MIN Jianjun (Kongzhi Yu Xinxi Jishu)
EMI suppression of high voltage DC end of motor drive system is one of the key technical problems in EMC design of electric vehicles. At present, EMI suppression for this port is usually based on empirical trial and error method in the industry, which lacks a set of accurate system level EMI simulation prediction models for quantitative EMC risk assessment. This paper studies EMI conducted interference paths of motor drive system, proposes a motor high-frequency equivalent circuit modeling method based on vector matching method and a system equivalent interference source modeling method based on time-domain extraction method, and establishes a conducted interference high-frequency circuit model of motor drive system. Experimental verification is carried out based on an actual passenger car electric drive system, and the overall error between predicted results and actual strategy results is less than 6 dB in the frequency range of 150 kHz ~ 10 MHz, which shows that the model can accurately predict the conducted interference level before and after EMI filtering suppression in the high voltage DC end of the system, and can effectively guide the forward EMC design of motor drive system.